PREVALENCE AND MANAGEMENT OF MALNUTRITION IN CHILDREN WITH CONGENITAL HEART DISEASE : A COMPREHENSIVE SYSTEMATIC REVIEW - Sriwaningsi, Lina; Oktadiputra, Ery (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Congenital heart disease is a congenital abnormality that affects the structure of the heart walls and vessels. Malnutrition has a significant impact on the likelihood of infection in children with congenital heart disease, which leads to poor treatment outcomes. The aim: The aim of this study to show about prevalence and management of malnutrition in children with congenital heart disease. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Nutrition is crucial in the treatment of chronic illness. It’s one of the most important factors affecting patients’ recovery after surgery and lowering the risk of infection in children with congenital heart disease.